Morphological Diversity Analysis using Existing and Endangered Banana Genotypes of Bangladesh (Journal of Bio-Science, 2026)
This study evaluated morphological diversity among 24 existing and endangered banana genotypes in Bangladesh from January 2023 to May 2025. Significant variation was observed in vegetative growth, flowering, harvesting time, and yield traits. Pseudo-stem height ranged from 2.24 m in Mehersagor to 4.53 m in Neyali, while base girth varied from 15.90 cm in Ramkela to 90.20 cm in Goma Atia. Yield attributes also differed markedly: Grand Naine produced the heaviest bunches (18.3 kg), Mehersagor the highest number of hands per bunch (12.8), and Champa the greatest number of fingers per hand (15.5). Individual finger weight was highest in Mehersagor (215.47 g) and lowest in Madna (74.90 g). In case of harvesting the longer period (366.30 days) found in Dudhsagor  whereas the shortest period (308.40 days) was recorded in Ramkela. Principal component analysis revealed that vegetative growth, crop duration, and yield traits contributed most to overall diversity, accounting for 75.45% of the cumulative variance across four components. These findings highlight substantial morphological and horticultural variation among Bangladeshi banana genotypes, underscoring their potential for cultivar selection, genetic conservation, and sustainable production strategies.J. Bio-Sci. 34(1): 88-99, 2026